2012
DOI: 10.1186/1477-7819-10-174
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in ovarian carcinoma and its correlation with clinicopathological features

Abstract: BackgroundMicroRNA (miRNA) expression is known to be deregulated in ovarian carcinomas. However, limited data is available about the miRNA expression pattern for the benign or borderline ovarian tumors as well as differential miRNA expression pattern associated with histological types, grades or clinical stages in ovarian carcinomas. We defined patterns of microRNA expression in tissues from normal, benign, borderline, and malignant ovarian tumors and explored the relationship between frequently deregulated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 44 publications
(61 reference statements)
2
70
0
1
Order By: Relevance
“…First, only tumors of serous histology were included in the present study and tumors of different origin may exhibit different patterns of miRNA expression. Previous profiling studies that included different histological types of ovarian cancer support this observation and reported different miRNA expression in serous, mucinous, endometrial and clear-cell types of cancer (33), as well as in borderline and invasive tumors (19). It has also been demonstrated that miR-146a expression was downregulated in highly metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…First, only tumors of serous histology were included in the present study and tumors of different origin may exhibit different patterns of miRNA expression. Previous profiling studies that included different histological types of ovarian cancer support this observation and reported different miRNA expression in serous, mucinous, endometrial and clear-cell types of cancer (33), as well as in borderline and invasive tumors (19). It has also been demonstrated that miR-146a expression was downregulated in highly metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 56%
“…The level of miR-370 expression was increased in FIGO stage I/II samples compared with FIGO stage III/IV tissue samples. Additionally, upregulated expression of miR-181d, miR-30c, miR-30d and miR-30e-3p significantly improved disease-free survival or OS (19). To the best of our knowledge, miR-146a expression has not been associated with clinical outcomes of ovarian cancer.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lee et al (15) previously reported that mir-30c had significantly lower expression in ovarian cancer tissue compared with normal ovarian tissue, and additional multivariate analysis revealed that patients with ovarian cancer mir-30c high expression had longer survival and overall survival rate. Zhou et al (16) revealed that miR-30c is a tumor suppressor gene that can inhibit the growth of endometrial cancer by targeting the expression of metastasis-associated 1.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al demonstrated that miR-30c overexpression inhibited metastasis-associated gene-1 (MTA1) (59). miR-30c is decreased in endometrial, ovarian, breast and gastric cancer (60)(61)(62)(63) and it is involved in carcinogenesis through its association with MTA1.…”
Section: Diagnosis Of Endometrial Cancer and Epigenetic Abnormalitiesmentioning
confidence: 99%